Real-World Outcomes and Healthcare Utilization of Lanadelumab in Spain: Insights from First Cohort of Difficult-to-Treat Hereditary Angioedema Cases - Inmaculada Sánchez-Machín; Ruperto González-Pérez; Elena Mederos-Luis; Sara García-Gil; Paloma Poza-Guedes (Allergies)
Background/Objectives: Hereditary angioedema (HAE) is a rare genetic condition marked by recurring episodes of intense swelling that affect the skin, gastrointestinal system, and airways. Lanadelumab, a monoclonal antibody that inhibits plasma kallikrein, is approved for long-term prophylaxis (LTP) in HAE patients, and has shown substantial efficacy in reducing disease symptoms. This single-center, retrospective study analyzed the real-world impact of lanadelumab on healthcare resource utilization, angioedema episode frequency, and quality of life (QoL) among adult HAE patients treated at the allergy department of Hospital Universitario de Canarias, Tenerife, Spain. Methods: This study included patients with a confirmed diagnosis of bradykinin-mediated HAE type 1 who were receiving lanadelumab 300 mg subcutaneously every two weeks, meeting specific inclusion criteria. A retrospective review of medical records from March 2021 to June 2024 assessed clinical outcomes under lanadelumab therapy, compared to prior clinical status. Key metrics included angioedema attack frequency, use of on-demand icatibant treatment, hospital visits, and QoL using the HAE-QoL questionnaire, alongside any adverse reactions associated with lanadelumab. Results: The investigation revealed a 75.3% reduction in hospital visits and a 94.1% decrease in angioedema episodes among HAE patients. Additionally, use of on-demand rescue medication (icatibant) was reduced by 61% (p < 0.05), while quality of life (QoL) scores improved from 62.2 to 99.5, with no significant adverse effects reported. Conclusions: Lanadelumab significantly reduced healthcare resource use and angioedema episodes, with marked improvements in quality of life. The reduced need for on-demand medication and hospital visits highlights lanadelumab’s value as an effective long-term prophylactic treatment with minimal adverse effects for HAE patients in real-world settings.